Hubungan Indeks Massa Tubuh Overweight dengan Gambaran Fatty Liver pada USG Abdomen di RSUD dr. Moewardi - Charismatika Syintia Dewi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Overweight increasing in the world is one result of the modernization of lifestyles, the increasing caloric intake and limited physical activity. Overweight is more realized to become of a person's risk for metabolism chronic disease. Fatty liver is increasingly recognized condition that also develop into chronic liver disease. This study aims to examine the relationship between overweight body mass index and fatty liver picture on USG Abdomen in RSUD dr. Moewardi. The study is expected to assist in diagnosis and treatment is more adequate and the prevention of fatty liver early on. Methods: This research is an analytical observational research with cross-sectional approach. Subjects were patients undergoing abdominal ultrasound Radiology Installation in RSUD dr. Moewardi in June 2012. Sampling was done after a fixed exposure sampling were selected based on inclusion and exclusion criteria of the sample. The obtained data were as many as 40 samples, taken immediately to see the results of focused abdominal ultrasound examination of heart and with a body mass index calculation derived from measurements of height and weight. Then samples were analyzed by Chi Square test and Odds Ratio test using the Statistical Product and Service Solution (SPSS ) 17.0 for Windows. Result: The data link overweight with a body mass index picture of fatty liver on abdominal ultrasound in RSUD dr. Moewardi was tested by Chi Square test bivariate analysis, obtained p = 0,011. Odds Ratio test was then performed to determine the strength of a causal relationship with OR = 5,571. Conclusion: There is a significant association between overweight body mass index with images of fatty liver on abdominal ultrasound (p = 0,011), where an overweight have a risk for developing fatty liver 5,571 times that of a normoweight or underweight. Keywords: fatty liver, body mass index, overweight, ultrasound